Assessment Of The Use Of E-Learning Resources By Lecturers In Colleges Of Education In Anambra State, Nigeria - S. E., Nwana; Ofoegbu, T. O.; Ikechukwu, Egbe Cajetan (Advances in Social Sciences Research Journal, 2017)
The study examined the use of e-learning resources by lecturers in colleges of education, Anambra State, Nigeria. The study is an empirical one. Four research questions guided the study. The population was made up of 340 lecturers out of which 200 were sampled and used for the study. The instrument for data collection was a 20 – item self-constructed questionnaire. It was validated by experts and has reliability co-efficient of 0.83. Data were analysed using the mean. The findings indicated that the lecturers are using e-learning facilities e.g. digital library to a high extent. Again they are using e-learning hardware e.g. computer to a high extent. Also they are using e-learning courseware e.g. CD-ROM and slides to a high extent. On the other hand, it was found that they are using e-learning packages to a low extent. Based on the findings, recommendations were made.